Food Enzyme Database (FEDA): a web application gathering information about food enzyme preparations available on the European market. (9th October 2021) - Deckers, Marie; Van Braeckel, Julien; Vanneste, Kevin; Deforce, Dieter; Fraiture, Marie-Alice; Roosens, Nancy h.c
Abstract: Following the European Commission No. 1332/2008 regulation and the consequent necessity of a scientific evaluation of food enzymes (FEs) for their approval for sale on the European Union market, many FE dossiers have been submitted to the European Commission and various documents currently co-exist. In order to centralize all relevant information in one structured location that is easily accessible to support enforcement laboratories and the competent authorities, we developed a web application, called Food Enzyme Database (FEDA). FEDA allows searching and collection of information originating from many different sources in one centralized portal. Queries can be performed using key information types, which include information on the producing company, production source (strain type, genetically modified microorganism status), type of enzyme protein and evaluation status with employed evaluation criteria. The database contains all current publicly available information. Centralizing all information coupled with intuitive searching functionality also allows the generation of general statistics regarding the current market situation. FEDA is open access and is freely available at the following location: https://feda.sciensano.be . Database URL : https://feda.sciensano.be